Direct observation methods: A practical guide for health researchers - Gemmae M. Fix; Bo Kim; Mollie A. Ruben; Megan B. McCullough (Elsevier, 2022)
Objective: To provide health research teams with a practical, methodologically rigorous guide on how to conduct direct observation. Methods: Synthesis of authors' observation-based teaching and research experiences in social sciences and health services research. Results: This article serves as a guide for making key decisions in studies involving direct observation. Study development begins with determining if observation methods are warranted or feasible. Deciding what and how to observe entails reviewing literature and defining what abstract, theoretically informed concepts look like in practice. Data collection tools help systematically record phenomena of interest. Interdisciplinary teams--that include relevant community members-- increase relevance, rigor and reliability, distribute work, and facilitate scheduling. Piloting systematizes data collection across the team and proactively addresses issues. Conclusion: Observation can elucidate phenomena germane to healthcare research questions by adding unique insights. Careful selection and sampling are critical to rigor. Phenomena like taboo behaviors or rare events are difficult to capture. A thoughtful protocol can preempt Institutional Review Board concerns. Innovation: This novel guide provides a practical adaptation of traditional approaches to observation to meet contemporary healthcare research teams' needs.